(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article provides information on how the names of the prophets Isa and Nuh mentioned in the Quran are used by authors in classical literature, as well as details about the lives of the prophets and literary art.